Human iPS Cell-Derived Germ Cells: Current Status and Clinical Potential - Ishii, Tetsuya (J Clin Med, 2014)
Recently, fertile spermatozoa and oocytes were generated from mouse induced pluripotent (iPS) cells using a combined in vitro and in vivo induction system. With regard to germ cell induction from human iPS cells, progress has been made particularly in the male germline, demonstrating in vitro generation of haploid, round spermatids. Although iPS-derived germ cells are expected to be developed to yield a form of assisted reproductive technology (ART) that can address unmet reproductive needs, genetic and/or epigenetic instabilities abound in iPS cell generation and germ cell induction. In addition, there is still room to improve the induction protocol in the female germline. However, rapid advances in stem cell research are likely to make such obstacles surmountable, potentially translating induced germ cells into the clinical setting in the immediate future. This review examines the current status of the induction of germ cells from human iPS cells and discusses the clinical potential, as well as future directions.